2019
DOI: 10.1002/cjoc.201900084
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance RuCl3 Catalyst Systems for Hydro‐Esterification of Methyl Formate and Ethylene

Abstract: Summary of main observation and conclusion RuCl3 catalyst system has many advantages for the hydro‐esterification of methyl formate and ethylene to methyl propionate. However, the unsatisfied performance restricts the development of this route. In this work, high‐performance RuCl3 catalyst systems (RuCl3‐[PPN]Cl‐Et4NI and RuCl3‐NaI) are firstly reported for this reaction. In RuCl3‐[PPN]Cl‐Et4NI catalyst system, the conversion of methyl formate and the selectivity to methyl propionate are 93.9% and 90.9% at mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…According to the work of Gómez‐Benítez et al, 35 DMF and Ru 3+ are coordinated to generate a new soluble complex, and the corresponding coordination atoms are the Ru atom and O atom in the amide structure of DMF. Li et al 36 also demonstrated that DMF and Ru 3+ are coordinated to generate a coordination compound. In order to verify the coordination between DMF and RuCl 3 in the process of reaction, 0.1876 g RuCl 3 is added to 20 mL DMF, completely reacting at room temperature and 180°C for 4 h to prepare liquid and solid samples.…”
Section: Resultsmentioning
confidence: 99%
“…According to the work of Gómez‐Benítez et al, 35 DMF and Ru 3+ are coordinated to generate a new soluble complex, and the corresponding coordination atoms are the Ru atom and O atom in the amide structure of DMF. Li et al 36 also demonstrated that DMF and Ru 3+ are coordinated to generate a coordination compound. In order to verify the coordination between DMF and RuCl 3 in the process of reaction, 0.1876 g RuCl 3 is added to 20 mL DMF, completely reacting at room temperature and 180°C for 4 h to prepare liquid and solid samples.…”
Section: Resultsmentioning
confidence: 99%